(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Matriculating in December 2013 from a co-educational government school in the Western Cape, the writer was the top student in the National Senior Certificate examinations for History in the Province. She shares her personal experience, by providing insight from a learner’s perspective, on the importance of studying history. She further shares her opinion on how a learner’s achievement can be directly affected by a teacher’s input and method of teaching. Based on her experience, she comments on the traits present in a superior teacher, teaching methods and techniques which she found effective in her learning experience, and what aspects of teaching contributed to her academic success, passion for history and its utility, and development as a person.